PEMBERIAN SEKAM PADI DAN PUPUK NPK MUTIARA 16:16:16 PADA TANAMAN LIDAH BUAYA (Aloe barbadensis mill) - Abdul Muis Zein; Siti Zahrah (DINAMIKA PERTANIAN, 2013)
This research was conducted at the Experimental Farm of Faculty of Agriculture Riau Islamic University Pekanbaru from April to August 2008. The research aim was to examine the effect of husk and NPK 16:16:16 fertilizer application on Aloe vera. The experimental with Completely Randomized Design for Factorial 4 x 4 was used. The first factor was application of husk, consisting of four levels such as 0, 2, 4, and 6 tonnes each of hectare, and second factor was different rate of NPK 16:16:16 fertilizer, consisting of four levels such as 0, 10, 20, 30 g each plant. The result of research indicates that interaction of treatment had a significant effect on plant height, length of leaf, number of leaf, and fresh weight of plant. The best treatment was application of 4 tonnes/ha of husk with 20 g/plant of NPK 16:16:16 fertilizer that produced 810.83 g fresh weight/plant with increase percentage was 76.27% than without husk and NPK 16:16:16 fertilizer.